Pendidik, Fungsi dan Tugasnya - Sitika, Achmad Junaedi; Rahmadian, Alia; Nindya, Nindya; Rahmadina, Firda; Novariyanti, Vani; Gustian, Rafi Dwi; Karhali, Ahmad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In the educational process, educators play a very important and decisive role in achieving educational goals. Educators are adults both by nature (parents) and by profession (becoming educators because of job duties) responsible for developing students. Parents as the first and main educators are obliged to educate their children because of the reasonableness of the responsibility of life itself. The second educator is because the position gets a temporary assignment from parents to educate their children (parents). Those who include educators because of their positions, for example, kindergarten to high school teachers, mentors in play groups, caregivers in orphanages and others. Educators are adults who guide children so that the child can lead to maturity. Educators are people who are responsible for the implementation of education with the target being students. Students experience their education in three environments, namely the family environment, school environment, and community environment. Therefore, those responsible for the education of students in the family environment are parents, in the school environment are teachers, in the community environment are people involved in educational activities, such as caregivers of orphans, mentors in play groups. Education takes place in association, as stated by Langeveld (1980): every association between adults (parents, teachers, etc.) and children is a field or a place where educational actions. Keywords : Islamic Education, Teachings of the Quran, Hadiths of Prophet Muhammad, Islamic Ethics/Morality, Concept of Islamic Education, Role of Parents in Education, Role of Teachers in Education, Student